2021
DOI: 10.1177/13623613211010072
|View full text |Cite
|
Sign up to set email alerts
|

Reduced engagement of visual attention in children with autism spectrum disorder

Abstract: A common example of social differences in autism spectrum disorder is poor modulation of reciprocal gaze, including reduced duration of eye contact and difficulty detecting the aim of another’s gaze. It remains unclear, however, whether such differences are specific to the social domain, or are instead indicative of broader alterations in processes of visual engagement and disengagement in autism spectrum disorder. To assess whether children with autism spectrum disorder experience altered engagement of visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
2
1
0
Order By: Relevance
“…Overall, autistic toddlers spent less time with their face oriented forward to the movies and exhibited higher blink rates compared to neurotypical toddlers. Our finding of reduced attentional engagement, regardless of stimulus type, is consistent with past work 18 , performed with consumer-grade eye-tracking tools, indicating that reduced visual engagement in autistic toddlers is not limited to social stimuli, but also extends to nonsocial stimuli. This finding is also consistent with eye tracking studies that reported that autistic toddlers exhibit lower overall sustained attention to any dynamic stimuli 19 .…”
Section: Discussionsupporting
confidence: 90%
“…Overall, autistic toddlers spent less time with their face oriented forward to the movies and exhibited higher blink rates compared to neurotypical toddlers. Our finding of reduced attentional engagement, regardless of stimulus type, is consistent with past work 18 , performed with consumer-grade eye-tracking tools, indicating that reduced visual engagement in autistic toddlers is not limited to social stimuli, but also extends to nonsocial stimuli. This finding is also consistent with eye tracking studies that reported that autistic toddlers exhibit lower overall sustained attention to any dynamic stimuli 19 .…”
Section: Discussionsupporting
confidence: 90%
“…In line with prior research [ 19 , 20 , 21 , 53 ], we found the expected effect that the SRT was significantly longer in the overlap condition compared to the baseline condition across both ASC and TD groups. The presence of the foveal stimulus in the overlap condition requires more effort to voluntarily disengage attention from and move the eyes to the peripheral target.…”
Section: Experiments 2: the Traditional Gap-overlap Task (Gop)supporting
confidence: 91%
“…Zalla et al (2016) found that saccadic latency, accuracy, velocity, and variability were not associated with the social subscales of the ADI‐R and ADOS across gap, overlap, and step conditions. Finally, McLaughlin et al (2021) did not identify an association between the gap effect (difference in latency between the gap and overlap conditions) and autism symptom severity (ADOS‐2 Total score) or social functioning (ADOS‐2 Social Communication score, SRS‐2 Total score [parent report]) across combinations of social and nonsocial central and peripheral stimuli.…”
Section: Resultsmentioning
confidence: 99%